Circadian regulation of metabolic, cell division, and cation transport promoters in the gastrointestinal bacterium Klebsiella aerogenes - Graniczkowska, Kinga B.; Paulose, Jiffin K.; Cassone, Vincent M. (Frontiers in Microbiology, 2023)
All eukaryotes and at least some prokaryotes express the capacity to anticipate and adapt to daily changes of light and temperature in their environments. These circadian programs are fundamental features of many forms of life. Cyanobacteria were the first prokaryotes to have demonstrated circadian gene expression. Recently, a circadian rhythm was also discovered in an unrelated bacterium, Klebsiella aerogenes, a human gut commensal and nosocomial pathogen. Here we characterize new clock-controlled genes with spatial differences in expression using a bacterial luciferase reporter. These include dephospho-coenzyme A kinase (coaE), manganese transporter, H-dependent (mntH) and a gene identified as filamenting temperature-sensitive mutant Z (ftsZ) Additionally, we show that K. aerogenes divides rhythmically in vitro and that these bacteria may alternate between exponential and stationary cells. Together, these findings provide a deeper understanding of K. aerogenes circadian clock and valuable insights for host-gut microbiota interactions and bacterial pathogenicity.